2012
DOI: 10.1109/tsp.2012.2199985
|View full text |Cite
|
Sign up to set email alerts
|

Second-Order Multidimensional ICA: Performance Analysis

Abstract: Independent component analysis (ICA) and blind source separation (BSS) deal with extracting a number of mutually independent elements from a set of observed linear mixtures. Motivated by various applications, this paper considers a more general and more flexible model: the sources can be partitioned into groups exhibiting dependence within a given group but independence between two different groups. We argue that this is tantamount to considering multidimensional components as opposed to the standard ICA case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
46
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 41 publications
1
46
0
Order By: Relevance
“…for any two m × m positive-definite matrices R 1 and R 2 , the log-likelihood for the model just described is [6] log p(…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…for any two m × m positive-definite matrices R 1 and R 2 , the log-likelihood for the model just described is [6] log p(…”
Section: Introductionmentioning
confidence: 99%
“…A closed-form expression for the CRLB and MSE is obtained in [6], where it is shown that this MSE is achievable also for non-Gaussian data.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we provide a linear optimal separating matrix for signal separation of mixed signals by maximizing the objective function. Compared to other signal separation methods, such as blind source separation (BSS) and independent component analysis (ICA) [9]- [11], the proposed method is more feasible and performs better according to computer simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Independent component analysis (ICA) is a statistical method for transforming an observed multidimensional random vector into components that are statistically as independent from each other as possible [1]. In a multi-input/multioutput (MIMO) context, the problem of ICA has found interesting solutions through the optimization of so-called contrast (objective) functions [2], many of which rely on higherorder statistics (e.g., the kurtosis contrast [3], [4]) or can be linked to higher-order statistics (e.g., the constant modulus contrast function [5]).…”
Section: Introductionmentioning
confidence: 99%